Pemerolehan Fonologi Bahasa Indonesia Anak Laki-Laki Usia 4 (Empat) Tahun - Fitriana, Riri Amanda (Ridwan Institute, 2021)
This study aims to describe the acquisition of phonology in the form of acquisition of vowels, consonants, and diphthongs. The method in this research is a qualitative method with a case study approach obtained by a 4 year old man. In this study it was found that the IHA had acquired complete vowel phonemes at the age of 4 years and most consonant had also been obtained. He has also mastered the sound of double vowels or diphthongs. While the fricative sound [f], the vibrating sound [r] was not mastered until the age of 4 years. Uniquely, IHA has its own ola if it finds consonant / l / and consonant / r / which is located at the end of a word. IHA will replace it with the phoneme // Å‹ //. This happens because the speech motor that IHA has is incomplete or not yet fully developed.